THE MANIFESTATION OF CHARACTER VALUES IN EFL TEXTBOOKS - Rukmayadi, Yazid (2016)
This study aims at investigating the manifestation of character values in the EFL textbooks. The study finds out what character values are manifested and how they are promoted in the textbooks. Generally, qualitative methodology is used in this study to identify and interpret the manifestation of character values in the EFL textbooks. However, some data are interpreted quantitatively in the form of descriptive statistic such as number of frequency and percentage. In this study, content analysis is considered a suitable method to achieve the goal since content analysis is a form of qualitative research in which researcher interprets the documents by giving comments and meaning around the topic. By using Shaaban and Gaith's and Ryan's framework, the study finds that there are 13 character values which are manifested in the EFL textbooks. They are; Confidence (13.7%), Creativity (10.6%), Politeness (13.2%), Love for peace (12.9%), Cooperation (11.5%), Being friendly (11%), Tolerance (11%), Social care (5.8%), Honesty (3.4%), Religiousness (2.6%), Thankfulness (1.9%), Care for environment (1.5%), and Spirit of nationality (0.9%). The study also finds that the values are promoted through the existences of five "E" methods namely Example, Explanation, Exhortation, Environment, and Experiences. Based on the result of the study, it is clear that values manifested in the textbooks are in line with the purpose of EFL learning as suggested by Shabaan (2005), Satz (2000), Brown (1997), etc. Finally, in order to achieve maximum implementation of character education, it is suggested that: 1) Teachers' book be equipped with more ample direction for teachers to conduct proper example, explanation, exhortation and specific assessment instruments to assess growth of the students' character value, 2) Further studies be conducted about the implementation of character education in the EFL classroom, and 3) Government to conduct specific training for teachers to educate character building.